Nab-paclitaxel versus paclitaxel for taxane acute pain syndrome in solid tumors: a systematic review and meta-analysis - Wei, Lai; Li, HongBo; Wang, ZhiYong (Frontiers in Oncology, 2026)
ObjectiveTo quantitatively compare the incidence and symptom-specific risk of taxane-associated acute pain syndrome (TAPS) between nab-paclitaxel (nab-PTX) and paclitaxel (PTX) in adults with solid tumors, with pre-specified stratification by dosing frequency.MethodsWe systematically searched PubMed, Embase and Cochrane Library (to November 30, 2023) for randomised trials comparing nab-PTX versus PTX. After excluding docetaxel and other taxanes, nine head-to-head RCTs (3,699 patients) were pooled using random-effects models. Odds ratios (OR) and risk ratios (RR) were calculated for arthralgia and myalgia, with subgroup analyses by q3w, q4w and weekly schedules. Risk of bias was assessed with RoB 2.0 and publication bias by funnel plots and Egger’s test.ResultsMyalgia incidence was significantly higher with nab-PTX (OR 1.25, 95% CI 1.06--1.48; I² = 0%), whereas arthralgia did not differ (OR 1.07, 0.91–1.25; I² = 0%). The excess myalgia was confined to the every-4-week (q4w, days 1,8,15) schedule (OR 1.32, 1.09–1.59; interaction p = 0.010), with no signal in q3w or weekly regimens. Up to one-quarter of q4w nab-PTX recipients experienced moderate-to-severe myalgia. Results were robust across sensitivity analyses and showed no publication bias.ConclusionsNab-PTX selectively increases acute myalgia risk by 25% versus PTX, exclusively within the q4w schedule, without affecting arthralgia. Dosing frequency, not cumulative dose, drives this symptom-specific toxicity. Clinicians should consider schedule selection and proactive analgesia when prescribing nab-PTX. https://www.crd.york.ac.uk/PROSPEROSystematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42023484814.